P413 ISCHEMIC ECG CHANGES, NOT ALWAYS CORONARY ISSUES. (18th May 2022) - Zanarelli, L; Canovi, L; Cardelli, L; Dal Passo, B; Frascaro, F; Piscitelli, L; Pallotti, M; Colletta, M; Casella, G
Abstract: Background: Many abdominal deseases can mimic cardiac symthoms at their presentation and they can lead to electrocardiographic (ECG) changes, acting as a confounding factor for the physichan during the diagnostic process. Case presentation: A 77–year–old man, former smoker, with high blood pressure not being treated, came to the emergency room with mesogastric pain and vomiting, since three hours before. The ECG showed a sinus rhythm, at 55 beats per minute and a slight elevation of the ST segment in the leads DII, DIII and aVF, evolving as T waves negativization in the same leads and flattening in V5– V6. Laboratory tests showed increasing Troponin I values from 23 to 277 ng / L. Because of this pathological context, the patient was taken to our Unit to perform a coronary angiography study in the hypothesis of acute myocardial infarction. The examination showed diffuse atheromatous lesions in the coronaries without haemodynamically significant stenosis. The patient developed fever during the hospitalization, abdominal CT study with contrast was performed, with a definitive diagnosis of acute cholecystitis and the patient was finally moved to the Internal Medicine ward. Conclusions: ECG alterations in acute cholecystitis are not specific, but some of them are recurrent: among these there are ischemic modifications affecting the ST segment or the T waves, widely described in the scientific literature. All these ECG modifications solve with the treatment of cholecystitis, whether conservative or surgical, without acting on the cardiological side in any way; on the other hand, they can lead to unnecessary diagnostic–therapeutic investigations, to a diagnosis'delay and to complications' onset. It is important for the clinician being able to consider abdominal pathology in case of diagnostic investigations' inconsistency. However, ST segment's changes during cholecystitis may deserve a cardiological study, as they are specific for acute myocardial infarction, especially in patients with high cardiovascular risk. This reminds to us, once again, the importance of anamnesis, physical examination and appropriate tests, to reach the correct diagnosis.